Diastolic blood pressure is a risk factor for peri-procedural stroke following carotid endarterectomy in asymptomatic patients - de Waard, D; de Borst, G; Bulbulia, R; Huibers, A; Halliday, A (Elsevier, 2017)
Background Carotid endarterectomy (CEA) prevents future stroke, but high peri-operative risks reduce net benefits. In symptomatic patients, diastolic hypertension has been causally related to procedural stroke following CEA. Aims We aimed to identify risk factors of peri-procedural stroke in asymptomatic patients and relate these to timing of surgery and mechanism of stroke. Methods In the first Asymptomatic Carotid Surgery Trial (ACST-1), 3120 patients with severe asymptomatic carotid stenosis were randomly assigned to CEA plus medical therapy or to medical therapy alone. In 1425 patients having their allocated surgery, baseline patient characteristics were analysed to identify factors associated with peri-procedural (<30 days) stroke or death. Multivariate analysis was performed on risk factors with a p-value <0.3 from univariate analysis. Event timing and mechanism of stroke were analysed using Chi-square tests. Results Peri-procedural stroke or death risk was low (42/1425 [2.9%]). Diastolic blood pressure at randomization was the only significant risk factor, after both univariate (OR=1.34 per 10 mmHg [95% CI 1.04 – 1.72]; p=.02) and multivariate analysis (OR 1.34 [95% CI 1.05 – 1.72]; p=0.02). In patients with diastolic hypertension (>90 mmHg) most strokes occurred during the procedure (67% versus 20%, p=0.02). Conclusion In ACST-1, diastolic blood pressure was the only independent risk factor associated with peri-procedural stroke or death. Good pre-operative control of blood pressure is important for ensuring safe carotid surgery.